Study on solar powered pump system design - SIPHAXAY, Khamphoungeun; RASSAVONG , Sybounheng; sengpasert , Boutthamaly; SISOMPHOU , Somphan (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
In this research would like to know the solar power pump is stable using or not, how to design the system of solar powered pump, how to control the system and what kind of designing is best for the system, so we have to do the research on solar pump efficient designing and using for system stability and after that we train to our students. In the research had design three solar powered pump system, first is DC solar powered pump without battery, the second system is DC solar powered pump with batter and the thirst system is AC solar powered pump with battery, for this research the solar powered pump system designing is useful and have enough energy for DC pump but not enough of AC pump so we have to install one more solar panel for AC pump. For energy production and using of DC pump without battery system depend on solar energy production, if solar array produced energy 2432 Wh and also a dc pump can use energy 2432Wh. The second system experiment, solar can produce the energy from 9 am to 4 pm is 3491.64Wh and DC pump had used energy in 7 hours is 2116.79 Wh, so the battery can strive energy for next day 1374.85 Wh per day. For the thirst system experiment, solar can produce the energy from 9 am to 4 pm is 3022.66Wh and AC pump had used energy in 7 hours is 3641.81Wh, it means that an electricity production is less than AC pump using, so the battery cannot store electricity for next day but battery has to supply more electricity 619.15Wh to the pump. The DC pump without battery system can produce water 748 liters less than two systems because of we have to restart motor every time when the weather cloudy, for the DC pump with battery connection is stable and can produced water 11,648 liter, and for AC pump with battery connection can store water more than DC pump system that we see in chart is 25,168 liter per day. The volume of water pumped by a solar-powered system in a given interval depends on the total amount of solar energy available in that period time. Specifically, the flow rate of the water pumped is determined by both the intensity of the solar energy available and the size of the PV array used to convert that solar energy into direct current (DC) electricity.